Penyuluhan Hukum Tentang Perlindungan Hukum Bagi Guru dalam Menjalankan Tugasnya di MIN 3 Pekanbaru - M. Musa; Zulkarnaini Umar; Syahrul Akmal Latief; Evi Yanti; Elsi Elvina; Rifqi Almahira; Rowi Aulia; Budi Kurnia (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2024)
Teachers in various regions of Indonesia currently always feel afraid, worried and anxious about carrying out their duties as educators. Recently, in several regions, teachers have been reported to law enforcement because they allegedly reprimanded/advised and hit their students at school, some even until he was sentenced to prison with the article applied being Article 351 of the Criminal Code concerning torture. Teachers at MIN 3 have become anxious about carrying out their duties as educators with such news that has been circulating on social media. Based on these problems, the service team from law faculty lecturers provides legal counseling related to protection for teachers in carrying out their duties. The legal counseling method used is the lecture method and PPT displays. The results of the service in the form of a legal counseling team succeeded in explaining first about legal protection for teachers in carrying out their duties as seen from Law No. 14 of 2005 concerning Teachers and Lecturers and then the next material was about restrictions on teachers teaching in Islam. This counseling is very important to provide information about teacher protection in carrying out their profession as educators which is protected by the state.